Climate Change and Hard-Soft Security Nexus:Future of Arctic Security Cooperation - Hossain, Kamrul (2021)
Climate change is arguably one of the most serious global problems of our time. Its implications are widespread touching every corner of the globe at various levels and in varied contexts. The implications are in most cases environmentally devastating, resulting in enormous concerns posing multidimensional threats to humans and communities at large. On the one hand, environmental changes in the Arctic causes human security threats to its diverse communities. On the other hand, consequences of climate change leads to new developments leading to geopolitical tensions as human activities are on the rise resulting in an increase in global presence in resource usage. Overall, the transformation of the Arctic debatably has implications of influencing global and regional security dynamics. As a result, both internal and external security dynamics in the Arctic conceive a hard-soft security nexus, engaging actors, both within and beyond the Arctic. Against this background, the following article explores the grounds of hard-soft security nexus in the Arctic. By examining some of the lessons from the recent past, the article investigates the future of regional security implications. Further, it analyses insights on the need for a multi-level regulatory, institutional, and participatory Arctic governance framework in response to hard-soft security nexus.